2019
DOI: 10.1186/s12884-019-2411-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gestational weight gain on perinatal outcomes among Chinese twin gestations based on Institute of Medicine guidelines

Abstract: Background Gestational weight gain (GWG) has implications for perinatal outcomes, the guidelines for maternal weight gain, however, remain understudied among twin pregnancies. This study aimed to assess the associations between perinatal outcomes and GWG among twin pregnancies, based on the US institute of Medicine (IOM) 2009 guidelines. Methods A retrospective cohort study of pregnant women with viable twins ≥26 weeks of gestation, was conducted in Foshan, China, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 29 publications
(48 reference statements)
5
47
0
Order By: Relevance
“…Flick et al [12] found a significant relation between neonatal intensive care unit admission and maternal obesity similar to our study. Similar to our study, in a study by Lin et al [13], the maternal weight gain was associated with neonatal intensive care unit admission and neonatal birth weight. In a study by Abide et al [14] also, the maternal weight gain was associated with neonatal intensive care unit admission and neonatal birth weight which were similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Flick et al [12] found a significant relation between neonatal intensive care unit admission and maternal obesity similar to our study. Similar to our study, in a study by Lin et al [13], the maternal weight gain was associated with neonatal intensive care unit admission and neonatal birth weight. In a study by Abide et al [14] also, the maternal weight gain was associated with neonatal intensive care unit admission and neonatal birth weight which were similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…The IOM lacks recommendations for underweight women (54). In addition, sample sizes of Chinese studies were relatively small and the impact of GWG on preterm birth was inconsistent (16,58). Lin et al found that the risk for patients with GWG below the IOM recommendations was 3.55 times risk for preterm birth before 37 weeks and 2.63 times risk for preterm birth before 35 weeks in Chinese twin pregnancies (16), but this study excluded underweight women.…”
Section: Discussionmentioning
confidence: 92%
“…GWG has been considered as a predictor in pregnancy outcomes in both singletons and multiple gestations in previous studies (15,16,56,57). Women with GWG below the recommendations of the IOM were at higher risk of small for gestation age and preterm birth, while GWG above the recommendations was associated with decreased risk for preterm birth (15,16,56). However, the impact of GWG and pregnancy outcomes were mainly based on patients from western countries and the results were inconsistent in twin pregnancies (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our study provided reliable results through multivariate analysis of factors such as maternal outcomes through binary logistic regression and neonatal outcomes by the GEE. Although the gestational age at birth, chorionicity, and fetal sex are important variables that can lead to adverse outcomes, many previous studies did not correct for them [34,[36][37][38][39]. In addition, GEE analysis, which is a method used to adjust for the correlation between twins, was not performed in previous studies despite its necessity [22,34,36,39].…”
Section: Discussionmentioning
confidence: 99%